Creative Cognition and Brain Network Dynamics. Issue 2 (February 2016) - Beaty, Roger E.; Benedek, Mathias; Silvia, Paul J.; Schacter, Daniel L.
Abstract : Creative thinking is central to the arts, sciences, and everyday life. How does the brain produce creative thought? A series of recently published papers has begun to provide insight into this question, reporting a strikingly similar pattern of brain activity and connectivity across a range of creative tasks and domains, from divergent thinking to poetry composition to musical improvisation. This research suggests that creative thought involves dynamic interactions of large-scale brain systems, with the most compelling finding being that the default and executive control networks, which can show an antagonistic relation, tend to cooperate during creative cognition and artistic performance. These findings have implications for understanding how brain networks interact to support complex cognitive processes, particularly those involving goal-directed, self-generated thought. Trends: Several recent neuroimaging studies have found that creative cognition involves increased cooperation of the default and executive control networks, brain systems linked to self-generated thought and cognitive control. Default–control network interactions occur during cognitive tasks that involve the generation and evaluation of creative ideas. This pattern of brain network connectivity has been reported across domain-general creative problem solving (e.g., divergent thinking) and domain-specific artistic performance (e.g., poetry composition, musical improvisation, and visual art production). Default network activity during creative cognition appears to reflect the spontaneous generation of candidate ideas, or potentially useful information derived from long-term memory. The control network may couple with the default network during idea generation or evaluation to constrain cognition to meet specific task goals.